2008
DOI: 10.1186/1752-1505-2-15
|View full text |Cite
|
Sign up to set email alerts
|

Providing HIV care in the aftermath of Kenya's post-election violence Medecins Sans Frontieres' lessons learned January – March 2008

Abstract: Kenya's post-election violence in early 2008 created considerable problems for health services, and in particular, those providing HIV care. It was feared that the disruptions in services would lead to widespread treatment interruption. MSF had been working in the Kibera slum for 10 years and was providing antiretroviral therapy to 1800 patients when the violence broke out. MSF responded to the crisis in a number of ways and managed to keep HIV services going. Treatment interruption was less than expected, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Kibera was a site of conflict during the post-election violence that followed the disputed Kenyan presidential election in December 2007; the tracing system greatly facilitated the identification of patients and continuation of treatment as soon as possible. 32 An important feature of the MSF defaulter tracing system is how the data suggest improvements to protocols and project implementation. The system has created an ongoing feedback loop between patients, social workers, clinicians and project staff that fosters discussion of and solutions to the challenges of adherence and retention.…”
Section: Discussionmentioning
confidence: 99%
“…Kibera was a site of conflict during the post-election violence that followed the disputed Kenyan presidential election in December 2007; the tracing system greatly facilitated the identification of patients and continuation of treatment as soon as possible. 32 An important feature of the MSF defaulter tracing system is how the data suggest improvements to protocols and project implementation. The system has created an ongoing feedback loop between patients, social workers, clinicians and project staff that fosters discussion of and solutions to the challenges of adherence and retention.…”
Section: Discussionmentioning
confidence: 99%
“…However MSF managed to keep TB/HIV services going during the post-election violence. 8 One out of the 86 (1%) cases contacted reported being unable to continue treatment due to the violence. Seven out of 27 (26%) controls that missed an appointment and were traced cited the violence as the reason for missing their appointment; all 27 subsequently returned to the clinic and completed their treatment.…”
Section: Outcomes Of the Defaulter Tracing Programmementioning
confidence: 99%
“…MSF's hotline in the Kibera slums of Nairobi reported mixed successes, with staff unprepared to answer non-HIV-related questions from patients and many patients unable to access the telephone number because they subscribed to another mobile provider. MSF concluded that an established hotline, prior to the violence, may have had greater success [46]. One research study team at the University of Nairobi/Manitoba was conducting a randomized trial of cell phone-based messaging to promote cART adherence at the time of the violence.…”
Section: Communicationsmentioning
confidence: 99%